2016
DOI: 10.1653/024.099.sp120
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Markers Differentiate between Mass-Reared and Wild Lepidoptera in Sterile Insect Technique Programs

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This usefulness is reinforced by the fact that the δ 13 C values of males did not differ from females, neither in flies reared on different larval diets nor in wild flies (Tables 1 and 3). This finding is in line with Hood-Nowotny et al [22] that also found no significant differences in isotope signatures between males and females of the cactus moth. However, it seems that sex differences depend on the species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This usefulness is reinforced by the fact that the δ 13 C values of males did not differ from females, neither in flies reared on different larval diets nor in wild flies (Tables 1 and 3). This finding is in line with Hood-Nowotny et al [22] that also found no significant differences in isotope signatures between males and females of the cactus moth. However, it seems that sex differences depend on the species.…”
Section: Discussionsupporting
confidence: 92%
“…As the isotopic signature of an animal reflects the isotopic composition of its food [15, 16], the carbon and nitrogen isotopic signature can be used to track feeding patterns of insects, for instance. Many studies have demonstrated that stable isotopes can be suitable intrinsic markers for mosquitoes [17, 18, 19], tsetse flies [20], moths [21, 22] and fruit flies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Insects undergo a behaviour-altering chain of processes during mass-rearing in an artificial environment and during handling and irradiation procedures before being released in the target area. The importance of mating compatibility between the released strain and the wild target population cannot be overemphasised and was already assessed with some fruit fly [ 31 ], tsetse fly [ 32 ] and Lepidoptera species [ 33 , 34 ]. Studies with the Mediterranean fruit fly C .…”
Section: Discussionmentioning
confidence: 99%
“…By enriching larval habitats with either 15 N or 13 C, we are elevating this rare form of element well above natural abundance levels which can serve as a label to differentiate the enriched mosquitoes from those that develop in unenriched environments. Stable isotopes have been widely used for identification purposes of different insects such as moths 12 , tsetse flies 13 , fruit flies 14 and mosquitoes [15][16][17] , and studies have shown minimal impacts on their physiology, behavior and ecology 18,19 . Stable isotopic marking of Anopheles gambiae s. l., Culex quinquefasciatus and Aedes spp.…”
mentioning
confidence: 99%